PENGARUH JUMLAH INDUSTRI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN SUMBAWA - Ira Anjani; Vivin Fitryani (Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to know the effect of the number of industries toward employment in Sumbawa Regency in 2011-2019. Type of this study was associative with a quantitative approach. The data used was secondary data obtained from cooperative and trade service (Diskoprindag) and the Central Bureau of Statistics of Sumbawa Regency. Data was collected using documentation techniques. The data analysis technique used was simple linear regression analysis. The results of this study showed that the variable of the number industries (X) had a significant effect toward labor absorption (Y). This conclusion was based on evidenced by the results of the t-value of 19.282 which was higher than the t table of 2.365 (19.282>2.365), the significance value of 0.000 was lower than 0.05 (0.00<0.05). Thus, Ho was rejected and Ha was accepted. This means that there was a significant effect of the number of industries toward employment in Sumbawa Regency in 2011-2019. The more the number of industries, the more labor that can be absorbed will also increase.